Chatbot advertising effectiveness: When does the message get through? - Van den Broeck, Evert; Zarouali, Brahim; Poels, Karolien (Computers in human behavior, 2019)
Chatbots on social networking sites are a recent innovation in computer-mediated marketing communication. In this study, 245 Facebook users between 18 and 35 years of age (Mage = 25.97, SD = 4.92) were asked to order tickets for the movies through Cinebot, a Facebook chatbot specifically built for the study. Afterwards, they were asked to evaluate their experiences via an online survey. The first purpose of this article was to investigate whether and how perceived helpfulness and usefulness of a chatbot consulted on the Facebook Messenger platform affected perceived intrusiveness of chatbot-initiated advertising in a later stage. In a second analysis, the relation between perceived intrusiveness and patronage intentions (i.e. purchase and recommendation intention of the product) was investigated. In addition, the role of message acceptance as a mediator and perceived message relevance as a moderator in this latter model were explored. As, to the best of our knowledge, our study is the first to investigate chatbot advertising, our research findings may hold important managerial implications. •Chatbots' helpfulness and usefulness negatively affect intrusiveness of chatbot ads.•In turn, Facebook chatbot ads' perceived intrusiveness predict patronage intentions.•However, message acceptance and product involvement explain this relationship\.